Tumour volume reduction following PET guided intensity modulated radiation therapy and temozolomide in IDH mutated anaplastic glioma. (January 2019) - Back, Michael; Jayamanne, Dasantha; Brazier, David; Bailey, Dale; Hsiao, Edward; Guo, Linxin; Wheeler, Helen
Highlights: Anaplastic glioma with IDH mutation is a relatively more favourable outcome than tumours that are IDH wildtype. This study assessed the radiological reduction in tumour volume in the first 12 months following IMRT and temozolomide. By month + 12 after IMRT median reduction was over 80% on T1 and T2Flair MRI sequences. Later relapses were distant and thus may not be influenced by extent of surgical resection. Where risk-benefit ratio of surgery is high, then IMRT and sequential temozolomide may provide effective volume reduction. Abstract: The role of maximal surgical debulking in isocitrate dehydrogenase (IDH) mutated anaplastic glioma prior to adjuvant radiation therapy remains uncertain. This study assessed the reduction in tumour volume following intensity modulated radiation therapy (IMRT) and temozolomide in this favourable and more responsive tumour pathology. 56 patients were managed from 2011 to 2014 and 53 had residual disease. To assess radiological response, tumour volumes were created on representative T1/T2Flair MRI sequences using identical slice-levels in three planes for pre-IMRT, month + 3 and month + 12 post-IMRT scans. Change in volumes was assessed between time periods. Progression-free survival (PFS) was calculated from start of radiotherapy. Median follow-up for survivors is 48.2 months. Pathology was anaplastic oligodendroglioma (AOD) and anaplastic astrocytoma IDH-mutated (AAmut) in 32 and 21 patients respectively. 93% received sequential chemotherapy. The median residual disease on T1 and T2Flair imaging was 9.7 cm 3 and 20.6 cm 3 . 17 patients relapsed for projected 5 year PFS of 74.9%; with 8 isolated relapses within initial surgical site. On MRI at month + 3, the median volume for T1 and T2Flair reduced by 69.4% and 67.3% respectively; which further decreased to 82.4% and 81.3% at month + 12. By month + 12, 69.2% and 62.2% of patients had >75% volume reduction. Patients with AOD had superior reduction at month + 3 compared with AAmut (p = 0.02); but equivalent reduction at month + 12 (p = 0.14). Thus, in patients with anaplastic glioma harbouring an IDH mutation, where an attempt at near-total resection may be associated with unacceptable morbidity, this data suggests that the radiation therapy may provide effective cytoreduction of residual disease.